The anthelmintic pyrantel acts as a low efficacious agonist and an open-channel blocker of mammalian acetylcholine receptors - de Rosa, Maria Jose (2001)
Pyrantel is an anthelmintic which acts as an agonist of nicotinic receptors (AChRs) of nematodes and exerts its therapeutic effects by depolarizing their muscle membranes. Here we explore at the single-channel level the action of pyrantel at mammalian muscle AChR. AChR currents are elicited by pyrantel. However, openings do not appear in clearly identifiable clusters over a range of pyrantel concentrations (1–300 μM). The mean open time decreases as a function of concentration, indicating an additional open-channel block. Single-channel recordings in the presence of high ACh concentrations and pyrantel demonstrate that the anthelmintic acts as a high-affinity open-channel blocker. When analyzed in terms of a sequential blocking scheme, the calculated forward rate constant for the blocking process is 8×107 M−1 s−1, the apparent dissociation constant is 8 μM at a membrane potential of −70 mV and the process is voltage dependent. Pyrantel displaces α-bungarotoxin binding but the concentration dependence of equilibrium binding is shifted towards higher concentrations with respect to that of ACh binding. Thus, by acting at the binding site pyrantel activates mammalian AChRs with low efficacy, and by sterical blockade of the pore, the activated channels are then rapidly inhibited.